Reliability and validity of the Chinese version of the Children's Fear Survey Schedule‐Dental Subscale. Issue 2 (15th April 2014) - Ma, Lin; Wang, Meng; Jing, Quan; Zhao, Jizhi; Wan, Kuo; Xu, Qun
<x xml:space="preserve">Abstract</x> Background The Children's Fear Survey Schedule‐Dental Subscale (CFSS‐DS) is a commonly used questionnaire that measures children's dental fears. Aim This study aimed to examine the reliability and validity of the Chinese version of the CFSS‐DS. Design The CFSS‐DS was translated into Chinese and administered to children in a dental office. The sample comprised 206 child patients aged 6–10 years, 42 of whom were selected for test–retest analysis. The behaviors of all 206 children were rated during their dental appointments and compared to their questionnaire results. Results The internal consistency (Cronbach's α) was 0.85, and the test–retest reliability (intraclass correlation) was 0.71. The Chinese version of the CFSS‐DS showed good criterion validity; children who were uncooperative on the Frankl Scale had higher mean CFSS‐DS scores (Z = 5.79). Through factorization, three factors emerged: (1) dental treatment, (2) hospital personnel, and (3) invasive dental procedures. Girls reported more fear than boys (21.79 vs 19.91), and children who had painful dental experiences reported more fear (30.87 vs 20.00). Conclusion These results suggest that the CFSS‐DS is reliable and valid and operates in China as it does in other cultures. Further studies should include school samples to evaluate children who may not go to the dentist.